Tinjauan Hukum Administrasi Negara Terhadap Pemenuhan Hak Penduduk Asli Papua dalam Konteks Otonomi Khusus - Nakeus Muid; Filep Wamafma; Isak Mansawan (JURNAL SULTAN: Riset Hukum Tata Negara, 2024)
This research investigates the effectiveness of the Special Autonomy Law (UU Otsus) in protecting and empowering the rights of indigenous West Papuans. Through a descriptive approach, this research aims to provide a comprehensive picture of the situation and present data systematically to strengthen the arguments and conclusions. Research data was collected from reliable sources such as government reports, academic journals, and NGO publications. Descriptive research methods were used to analyze the data and elaborate on the findings. The results show that the Special Autonomy Law has provided some progress in the recognition of customary rights, improved infrastructure, improved living standards, and political participation of the people of West Papua. However, there are still challenges in implementation, such as unclear mechanisms, limited resources, corruption, prolonged conflicts, and the lack of understanding of indigenous peoples about their rights. Therefore, increased transparency, public participation, close monitoring, peaceful conflict resolution, and improved understanding of indigenous peoples are needed to improve the effectiveness of legal protection of indigenous rights in West Papua.